2013
DOI: 10.2987/12-6307r.1
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput Mosquito and Fly Bioassay System for Natural and Artificial Substrates Treated with Residual Insecticides

Abstract: A high-throughput bioassay system to evaluate the efficacy of residual pesticides against mosquitoes and muscid flies with minimal insect handling was developed. The system consisted of 4 components made of readily available materials: 1) a CO2 anaesthetizing chamber, 2) a specialized aspirator, 3) a cylindrical flat-bottomed glass bioassay chamber assembly, and 4) a customized rack.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Similar analyses between treated and untreated enclosures with each spatial repellent present also showed no statistical differences. Subsequent laboratory analysis of cuttings taken the day of the residual pesticide treatment of the ULCANS enclosures using the bioassay process described in Aldridge et al (2013) showed a mean effect of only 30.2% corrected 24-h mortality (Abbott 1925) on susceptible colony-reared Cx. quinquefasciatus.…”
mentioning
confidence: 99%
“…Similar analyses between treated and untreated enclosures with each spatial repellent present also showed no statistical differences. Subsequent laboratory analysis of cuttings taken the day of the residual pesticide treatment of the ULCANS enclosures using the bioassay process described in Aldridge et al (2013) showed a mean effect of only 30.2% corrected 24-h mortality (Abbott 1925) on susceptible colony-reared Cx. quinquefasciatus.…”
mentioning
confidence: 99%
“…First, we placed a CDC trap baited with light and CO 2 (dry ice) for 24 hr in the center of the protected space in all 16 HESCO perimeters to periodically survey the overnight penetration of the perimeters by natural populations of medically important mosquitoes. Second, at the time of mosquito collection we cut ~15 cm x 15 cm samples of geotextile from the inside and outside facing surfaces of each perimeter and exposed them to laboratory colony Culex quinquefasciatus females in glass tube bioassays at the USDA Agricultural Research Service Center for Medical, Agricultural, and Veterinary Entomology (CMAVE) following the methods and colony description of Aldridge et al (2012Aldridge et al ( , 2013 and Britch et al (2009Britch et al ( , 2010Britch et al ( , 2011. We stored each cutting separately in labeled re-sealable bags to minimize opportunity for cross-contamination of samples.…”
Section: B Amentioning
confidence: 99%
“…Set the timer for 4 min, which is the approximate time before mosquitoes will become active again. Use a pistol aspirator 15,16 or soft-touch insect forceps to pick out batches of 20 adult females and immediately place them in the waiting open sentinel cages. Once all females have been picked out of the anaesthetized batch, use a separate mechanical aspirator to collect all remaining male mosquitoes which will be destroyed by freezing.…”
Section: Sentinel Insect Rearing and Sentinel Cage Preparationsmentioning
confidence: 99%